2021
DOI: 10.3390/toxins13110737
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Effects of Weather Conditions on Cereal Grain Contamination with Deoxynivalenol in the Baltic Sea Region

Abstract: Fusarium head blight (FHB) is one of the most serious diseases of small-grain cereals worldwide, resulting in yield reduction and an accumulation of the mycotoxin deoxynivalenol (DON) in grain. Weather conditions are known to have a significant effect on the ability of fusaria to infect cereals and produce toxins. In the past 10 years, severe outbreaks of FHB, and grain DON contamination exceeding the EU health safety limits, have occurred in countries in the Baltic Sea region. In this study, extensive data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 65 publications
0
7
0
4
Order By: Relevance
“…Pathogenic fungal species produce mycotoxins that, under favorable weather conditions, can be accumulated in grains directly after infection. This group of compounds includes DON, which is one of the most frequently identified mycotoxins in crops and plant-based foods in Poland [39]. In this study, DON was detected in all the samples of winter wheat grains within a concentration range of 4.00-311 µg/kg.…”
Section: Discussionmentioning
confidence: 49%
“…Pathogenic fungal species produce mycotoxins that, under favorable weather conditions, can be accumulated in grains directly after infection. This group of compounds includes DON, which is one of the most frequently identified mycotoxins in crops and plant-based foods in Poland [39]. In this study, DON was detected in all the samples of winter wheat grains within a concentration range of 4.00-311 µg/kg.…”
Section: Discussionmentioning
confidence: 49%
“…In a recent study in the Baltic countries, precipitation at ripening was identified as a risk factor for DON contamination in several crops (Marzec-Schmidt et al 2021 ). This indicates that delayed harvest may be especially problematic under rainy conditions, or that rain is often causing delayed harvest, and the effect of these two factors may be difficult to separate.…”
Section: Discussionmentioning
confidence: 99%
“…Zainfekowane ziarniaki, nawet wyglądające na zdrowe, mogą być skażone mykotoksynami (Cowger i Arrellano, 2010;Del Ponte i in., 2007). Nasilenie fuzariozy kłosów zależy przede wszystkim od warunków pogodowych podczas kwitnienia a także innych czynników agrotechnicznych, takich jak odporność odmian, sposób uprawy gleby, przedplon i inne (Klem i in., 2007;Marzec-Schmidt i in., 2021;West i in., 2012). Na zawartość mykotoksyn w ziarnie wpływ mają także warunki pogodowe po kwitnieniu do momentu zbiorów ziarna (Cowger i in., 2009).…”
Section: Występowanie I Etiologia Fuzariozy Kłosówunclassified
“…Głównymi sprawcami fuzariozy kłosów są następujące gatunki Fusarium: F. culmorum, F. graminearum i F. avenaceum (Bilska i in., 2018;Bottalico, 1998;Bottalico i Perrone, 2002;Góral i in., 2021;Iwaniuk i in. 2018;Kuzdraliński i in.…”
Section: Gatunki Fusarium Powodujące Fuzariozę Kłosówunclassified
See 1 more Smart Citation